2017
DOI: 10.1021/acs.cgd.7b00365
|View full text |Cite
|
Sign up to set email alerts
|

Indium Incorporation Induced Morphological Evolution and Strain Relaxation of High Indium Content InGaN Epilayers Grown by Metal–Organic Chemical Vapor Deposition

Abstract: The indium (In) incorporation induced morphological evolution and strain relaxation of high In content InGaN epilayers grown by metal–organic chemical vapor deposition (MOCVD) were investigated. With the decrease of growth temperature from 753 to 627 °C, In incorporation increases from 0.10 to 0.42, and the surface morphology evolves from initially mound-like three-dimensional surface roughness to progressive smoothness. Such morphology evolution mechanism can be well accounted for by a self-regulating model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Particularly in sample B, the V-defects density dramatically decreases and trench defects density increases concomitantly. A rather high crack like defects was also observed while compared to the other two samples [24,26,48]. These kinds of crack like defects were certainly to mediate the high density trench defects from the similar factors observed in literature [49].…”
Section: Morphological Studiessupporting
confidence: 70%
See 4 more Smart Citations
“…Particularly in sample B, the V-defects density dramatically decreases and trench defects density increases concomitantly. A rather high crack like defects was also observed while compared to the other two samples [24,26,48]. These kinds of crack like defects were certainly to mediate the high density trench defects from the similar factors observed in literature [49].…”
Section: Morphological Studiessupporting
confidence: 70%
“…It was also observed that, the distribution of 3D island was without obvious flat zones on the surface. In this phenomenon, while increasing the Indium flow rate, more indium incorporation occurred which results in increasing the misfit strain in the layer, this accelerate the formation of 3D islands [24]. Figure 6 clearly shows that there is a random change in the surface morphology of InGaN samples grown by MOCVD.…”
Section: Morphological Studiesmentioning
confidence: 93%
See 3 more Smart Citations